The role of labor demand in the labor market effects of a pension reform - Johannes Geyer; Peter Haan; Svenja Lorenz; Mona Pfister; Thomas Zwick (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper shows that labor demand plays an important role in the labor market reactions of older women affected by pension deductions for early retirement. Based on a large representative sample of the German workforce (SIAB), we calculate the consequences of individual financial incentive changes caused by a pension reform in Germany on employment, unemployment, and partial retirement. The reform reduces financial incentives for early retirement. In line with labor demand theory, we show that employers with a high share of older worker inflow compared with the share of younger worker inflow, employers in sectors with a high share of collective bargaining agreements, and employers in sectors with few investments in research and development are more responsive to their employees' demand to stay longer in the labor market. These employer groups mainly offer their older employees the option of staying longer in partial retirement instead of forcing them into unemployment before retirement.
Keywords: J14; J18; J22; J26; H31; 330; pension reform; labor demand effects; early retirement; employer heterogeneity